Hospital admissions for acute drug poisoning in adults and children: a 7-year retrospective analysis of hospital discharges at a tertiary center - Wang, Daniel; Camacho-Arteaga, Lina; Muñoz Gallarín, Rosario; Danés, Immaculada; Agustí Escasany, Antònia (Frontiers in Toxicology, 2025)
BackgroundDrug poisoning is a growing public health concern, affecting both adult and pediatric populations. The COVID-19 pandemic has further influenced the incidence and patterns of these episodes. This study describes the clinical and epidemiological characteristics of drug poisoning episodes in adult and pediatric patients treated at a tertiary hospital in Spain between 2018 and 2024.Materials and methodsThis retrospective, observational, single-center study used data from the Spanish Minimum Basic Data Set of Hospital Discharges (CMBD-AH). All hospitalizations coded with a diagnosis of drug poisoning (ICD-10-ES: T36–T50) were included. Variables analyzed included demographics, type of admission, drug class involved, intentionality, length of stay, ICU admission and duration, and clinical outcomes.ResultsA total of 2,989 episodes with at least one drug poisoning code were identified in 2,481 patients (85.7% adults; 14.3% pediatric). The median age was 55 years in adults and 14 years in pediatric patients. Females predominated in both groups. Self-poisoning was the most frequent intentionality (52.4% in adults; 54.7% in pediatric patients), while accidental poisonings were more common in pediatric patients under 12 and adults over 60. Benzodiazepines were the most frequently involved drug-class across all age groups; in pediatric self-poisoning, paracetamol was most commonly implicated. ICU admission was required in 9.6% of pediatric and 9.2% of adult episodes. Mortality was reported in 3.3% of adult and 0.5% of pediatric episodes. Additionally, 12.5% of patients experienced recurrent episodes. A significant post-COVID increase in poisoning episodes was observed (p < 0.001).ConclusionAlthough drug poisoning represented only 1.7% of all hospital discharges, it posed a substantial burden due to its frequency, recurrence, and ICU requirements. The CMBD-AH is a valuable tool for characterizing drug-related hospitalizations across age groups. Strengthened toxicovigilance, targeted prevention strategies, and early mental health interventions are essential to reduce its impact on healthcare systems.